Legionella antibiotic susceptibility testing: is it time for international standardization and evidence-based guidance?. (20th February 2021) - Portal, Edward; Descours, Ghislaine; Ginevra, Christophe; Mentasti, Massimo; Afshar, Baharak; Chand, Meera; Day, Jessica; Echahidi, Fedoua; Franzin, Laura; Gaia, Valeria; Lück, Christian; Meghraoui, Alaeddine; et al.
Abstract: Legionella pneumophila, a Gram-negative bacillus, is the causative agent of Legionnaire's disease, a form of severe community-acquired pneumonia. Infection can have high morbidity, with a high proportion of patients requiring ICU admission, and up to 10% mortality, which is exacerbated by the lack of efficacy of typical empirical antibiotic therapy against Legionella spp. The fastidious nature of the entire Legionellaceae family historically required inclusion of activated charcoal in the solid medium to remove growth inhibitors, which inherently interferes with accurate antimicrobial susceptibility determination, an acknowledged methodological shortfall, now rectified by a new solid medium that gives results comparable to those of microbroth dilution. Here, as an international Legionella community (with authors representing various international reference laboratories, countries and clinical stakeholders for diagnosis and treatment of legionellosis), we set out recommendations for the standardization of antimicrobial susceptibility testing methods, guidelines and reference strains to facilitate an improved era of antibiotic resistance determination.